Indiana Steinhardt and the Quest for Quasicrystals : A Conversation with Paul Steinhardt. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Paul Steinhardt, the Albert Einstein Professor of Science and Director of the Center for Theoretical Science at Princeton University. This wide-ranging conversation provides a comprehensive account of a marvellous scientific adventure story in the quest for a natural quasicrystal. You will be taken on a fascinating ride through the physics of materials, from theory, to the laboratory, to the discovery of a new state of matter, that culminated in Paul Steinhardt's dramatic Siberian expedition. Paul Steinhardt talks.